METHODOLOGICAL APPROACH FOR IDENTIFYING AND MEASURING THE ECONOMIC BENEFITS OF TRADE FACILITATION THROUGH THE PORTS AND LANDS OF ARAB COUNTRIES (Malaysian Journal of Civil Engineering, 2018)
This research paper aims to develop a methodological approach that can be employed to identify and measure the economic benefits of trade facilitation procedures among the ports and lands of Arab countries. The research developed the methodology framework, the benefit algorithm, and the analyses. The developed approach is then applied to the case of Lebanon, Syria, and Jordan to derive the obtained benefits for each country as a result of improving trade facilitation conditions of the three countries under several proposed scenarios. The results obtained show that easing trade through the proposed scenarios of improvement would yield significant economic benefits in various sectors of the economy. The methodological approach can be considered as a generic tool kit that can be utilized for many trade corridors, routes, and countries as required.